Oil-water separation process analysis in hydrocyclone via CFD (Research, Society and Development, 2020)
Hydrocyclones are equipment used in oil-water separation processes. They are considered to be efficient, compact, safe, of simple construction and maintenance, and low cost, when compared to other equipment used in similar application. Therefore, this work aims to numerically analyze the separation process of an oil-water mixture in hydrocyclone, regarding to the fluid dynamic aspect. For the numerical solution of the governing equations, the Ansys CFX software was used. Results of the pressure and volumetric fraction fields of the oil phase, and the separation performance of the equipment are presented and analyzed. From the results obtained, it was found that the highest pressures occur near the walls and the entrance of the equipment, that the largest volumetric fractions of the oil occur in the central region and close to the outlet of the hydrocyclone, and that this equipment presented separation efficiency greater than 99.8%.